2023
DOI: 10.1088/1741-4326/acc7b8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of plasma beta effects on the island divertor transport in the standard configuration of W7-X

Abstract: The influence of plasma beta effects on the edge plasma transport in the Wendelstein 7-X standard configuration is studied systematically by using EMC3-EIRENE combined with a 3D equilibrium code named HINT. The magnetic topology changes induced by plasma beta effects are significantly reflected in plasma transport behaviors and heat flux patterns on divertor targets. After validating the modeling strategy by comparisons with experimental data, the extended simulations for high performance plasmas show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…By using the vacuum approximation for the magnetic equilibrium, the effect of plasma currents and high β effects are not included although they influence the plasma as shown in [19]. In [20] it has been shown that these high β effects are moderate for limited heating powers which are used in the presented work. Besides, the effects of drift flows which cause an asymmetry in the plasma between the upper and lower parts of the modules [21,22] is not implemented in the current version of EMC3-EIRENE.…”
Section: Simulation Setupmentioning
confidence: 99%
“…By using the vacuum approximation for the magnetic equilibrium, the effect of plasma currents and high β effects are not included although they influence the plasma as shown in [19]. In [20] it has been shown that these high β effects are moderate for limited heating powers which are used in the presented work. Besides, the effects of drift flows which cause an asymmetry in the plasma between the upper and lower parts of the modules [21,22] is not implemented in the current version of EMC3-EIRENE.…”
Section: Simulation Setupmentioning
confidence: 99%